One-pot solvothermal synthesis of S doped BiOCl for solar water oxidation1. Issue 58 (25th June 2015) - Jiang, Zaiyong; Liu, Yuanyuan; Jing, Tao; Huang, Baibiao; Wang, Zeyan; Zhang, Xiaoyang; Qin, Xiaoyan; Dai, Ying
<x xml:space="preserve">Abstract</x> S doping significantly improves the photocatalytic activity of BiOCl, due to the two impurity states induced by S.